Observation of the stress distribution in crushed glass with applications to soil reinforcement - Dyer, M (1985)
The research described in this dissertation follows on from the study made by Jewell (1980)into the effects of tensile reinforcement on the mechanical behaviour of sand. For this study Jewell used the direct shear test with reinforcement placed about the central plane as shown in fig. 1.1. The direct shear test was chosen for the following reasons. (1) The reinforcement variables could be better controlled and examined in a unit cell test than in modular field studies of soil reinforcement systems. (2) The pattern of deformation is similar to that experienced by soil in which a rupture band develops, with the principal axes of stress, strain and strain increment free to rotate as is the case in model and field structures. (3) The overall shear strength of the sample is measured directly at the boundaries of the apparatus. The direct shear tests were monitored by boundary measurements and internal measurements using a radiographic technique. The findings are outlined below with reference made to relevant observations by other researchers. 1) The optimum orientation for a relatively flexible steel grid was found to be approximately along the direction of principal tensile strains in the unreinforced sand, see fig.1.2. This indicated that the reinforcement functioned by limiting tensile strains in the sand. McGown et al. (1978) obtained a similar result for plane strain cell tests on sand containing a single layer of flexible reinforcement. However in both studies the reinforcement was observed to waken the sand. Jewell recognized weakening to occur when the steel grid was placed along the direction of principal compressive strains in the unreinforced sand. This was attributed to a reduction in vertical effective stress. McGown et al. observed weakening of the sand when the reinforcement orientation approached the rupture band which developed in the sand alone. This was recognized to be the direction of zero-extension in the unreinforced sand. The weakening was linked to a lower bond between soil and reinforcement than soil alone. 2) Internal strains determined by Jewell showed the tensile reinforcement modified strains in the sand over a well defined zone, see fig.1.3. This resulted in a significant rotation of principal axes of strain increment, with the bond of major strains which developed across the centre of the box in the unreinforced sand being prohibited from forming. This agreed with boundary measurements, indicating the reinforcement functioned by limiting tensile strains in the sand. Consequently a less favourable mode of failure took place. The limit of rotation of principal axes of strain increment was understood to be the alignment of a direction of zero-extension in the sand with the reinforcement. These findings agree with the ideas expressed by Basset and Last (1978) on the mode of action of tensile reinforcement, which in particular was related to the effect of tensile reinforcement on the strain field in a reinforced earth wall as shown in fig.1.4. 3) For efficient use of tensile reinforcement it was demonstrated that the bond with sand should be as high as possible. This could be achieved by roughening the surface. Alternatively, the bond was improved by introducing openings or apertures in the reinforcement, changing the shape to a grid. It appeared that the bond for a suitably proportioned grid could be as high as for a fully roughened surface. 4) The longitudinal stiffness of tensile reinforcement was observed to affect the magnitude and rate of increase in strength in the direct shear tests. The rupture strain of tensile reinforcement relative to maximum tensile strains of the soil, under the same operational stress conditions, have also been observed to influence the reinforcing effect in terms of its limiting behaviour, i.e. whether brittle or ductile (McGown, et al. 1978). With regards to the performance of reinforced earth walls, Al-Hussanini and Perry (1976) observed that steel reinforced strips produced a stiffer and stronger structure than a more extensible fabric reinforcement, even though surface roughness was less. The importance of reinforcement tensile stiffness is recognized in limit equilibrium designs for tensile reinforced soil structures by limiting the available reinforcement force to the tensile strains that can develop in the soil (e.g. Jewell 1985). For highly structured non-woven and composite geotextiles, McGown et al. (1982) demonstrated that the stress-strain behaviour can be significantly affected by soil confinement. Testing wider strips in isolation was not found to replicate the effects of soil confinement. Another factor which needs to be considered when assessing the tensile property of a polymer reinforcement is creep. McGown et al. (1984) illustrated an appropriate method of interpreting creep data using isochronous curves, which enable long term laboratory test data to be extrapolated to the design life of the soil structure. 5) The strain and hence stress fields in the reinforced direct shear tests have been shown to be complex and non-uniform. However Jewell successfully modelled the variation of reinforcing effect for tensile reinforcement at different orientations by using a simple limit equilibrium analysis, see fig.1.5. The effect of the tensile reinforcement force was represented as: - an increase in the normal effective stress acting on the central plane of the box due to the normal component of the force and - a reduction in the applied shear stress due to the parallel component of the force to the central plane. Subsequently this analysis has been applied to limit equilibrium design methods for reinforcing soil retaining walls and embankments, Jewell et al. 1984, and Jewell 1982 respectively. 6) A reduction in the reinforcing effect for individual reinforcement due to the presence of other reinforcement was observed in the shear box. This loss of efficiency of individual reinforcement was termed interference. Interference between tensile reinforcement has also been studied by Guilloux et al. (1979) for the pull-out resistance from soil. However interference between reinforcement has yet to be introduced into a limit equilibrium design method.